Online Fun Physics Experiments Untuk Meningkatkan Motivasi Belajar Siswa Sekolah Dasar Yayasan Mutiara Bunda Jember - Risse Entikaria Rachmanita; Zeni Ulma (Indonesian Journal Publisher, 2022)
Distance Learning which is currently being implemented as a result of the Covid-19 pandemic which has lasted for almost 1.5 years has caused psychological problems for students. The problems that arise include boredom due to monotonous learning, less interactive, and piling tasks. The level of education that is quite affected due to the implementation of Distance Learning is elementary school education. To overcome these problems, it is necessary to do a learning that is able to restore student motivation in learning. Mutiara Bunda Jember Foundation in collaboration with Renewable Energy Engineering lecturers at the Politeknik Negeri Jember held an interesting and interactive lesson entitled